2021
DOI: 10.2174/1745017902117010010
|View full text |Cite
|
Sign up to set email alerts
|

The Malaysian Women's Experience of Care and Management of Postnatal Depression

Abstract: Objectives: Early detection and intervention for Maternal Postnatal Depression (PND) are imperative to prevent devastating consequences for mothers, babies, and families. However, there are no guidelines that explicitly focus on the management of PND in Malaysia. Consequently, it is unclear whether women with PND are receiving proper care and treatment. Therefore, this study aimed to explore Malaysian Women's experience in managing PND symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The strong social support received by postpartum mothers from the people around them such as partners, parents, family, friends, and the surrounding environment greatly affect the minimization of the incidence of postpartum depression in mothers after giving birth. This explanation is in line with research by Arifin et al, (2021) which states that one way to overcome postpartum depression is to create a stress coping strategy, which strategy can be structured with the help and support of partners and people around the mother. Another study stated that the weak social support that mothers received after giving birth could increase the incidence of postpartum depression (aOR= 1.79; 95% CI= 0.92 to 3.48) (Sheeba et al, 2019).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The strong social support received by postpartum mothers from the people around them such as partners, parents, family, friends, and the surrounding environment greatly affect the minimization of the incidence of postpartum depression in mothers after giving birth. This explanation is in line with research by Arifin et al, (2021) which states that one way to overcome postpartum depression is to create a stress coping strategy, which strategy can be structured with the help and support of partners and people around the mother. Another study stated that the weak social support that mothers received after giving birth could increase the incidence of postpartum depression (aOR= 1.79; 95% CI= 0.92 to 3.48) (Sheeba et al, 2019).…”
Section: Resultssupporting
confidence: 80%
“…The etiology of postpartum depression is a decrease in estrogen and progesterone as well as epigenetic and neuroendocrine changes. Symptoms include depression, loss of interest, lack of energy, insomnia or hypersomnia, difficulty concentrating, persistent doubts, changes in appetite, lethargy, suicidal ideation or attempts, feelings of unworthiness and guilt (Arifin et al, 2021).…”
mentioning
confidence: 99%
“…Among the symptoms reported by the women were 'loss of excitement', 'easily irritated', and 'feeling of not being normal.' Somatic symptoms such as loss of appetite and weight stated in the DSM-V were not widely reported [15]. Meanwhile, Vanderkruik et al [2] reported that the clinical features of postnatal psychosis were mood-incongruent delusions, hallucinations or delusions of control which were often associated with infant and self-harm.…”
Section: Discussionmentioning
confidence: 99%